New dihydropyrimidin-2(1H)-one based Hsp90 C-terminal inhibitors. Issue 85 (30th August 2016) - Terracciano, S.; Foglia, A.; Chini, M. G.; Vaccaro, M. C.; Russo, A.; Piaz, F. Dal; Saturnino, C.; Riccio, R.; Bifulco, G.; Bruno, I.
Abstract : The inhibition of the C-terminal domain of heat shock protein 90 (Hsp90) is emerging as a novel strategy for cancer therapy, therefore the identification of a new class of C-terminal inhibitors is strongly required. Abstract : The inhibition of the C-terminal domain of heat shock protein 90 (Hsp90) is emerging as a novel strategy for cancer therapy, therefore the identification of a new class of C-terminal inhibitors is strongly required, also in consideration that to date only nature-inspired molecules have been largely expanded. Our recent discovery of potent antiproliferative dihydropyrimidone based C-terminal Hsp90 inhibitor (1, IC50 = 50.8 ± 0.2 μM and 20.8 ± 0.3 μM in A375 and Jurkat cell lines, respectively) drove us to further explore this very promising pharmacophoric core. In this study, we identified a new set of DHPM-derivatives that exhibited antiproliferative activity against two cancer lines by their modulation of Hsp90 C-terminus without inducing the undesired heat shock response. Our results strongly outline the high sensitivity of the Biginelli scaffold to structural decorations allowing us to point out also that small variations can deeply influence biological activity.